Non-contact and label-free biomechanical imaging: Stimulated Brillouin microscopy and beyond - Shi, Chenjun; Zhang, Hongyuan; Zhang, Jitao (Frontiers in Physics, 2023)
Brillouin microscopy based on spontaneous Brillouin scattering has emerged as a unique elastography technique because of its merit of noncontact, label-free, and high-resolution mechanical imaging of biological cell and tissue. Recently, several new optical modalities based on stimulated Brillouin scattering have been developed for biomechanical research. As the scattering efficiency of the stimulated process is much higher than its counterpart in the spontaneous process, stimulated Brillouin-based methods have the potential to significantly improve the speed and spectral resolution of existing Brillouin microscopy. Here, we review the ongoing technological advancements of three methods, including continuous wave stimulated Brillouin microscopy, impulsive stimulated Brillouin microscopy, and laser-induced picosecond ultrasonics. We describe the physical principle, the representative instrumentation, and biological application of each method. We further discuss the current limitations as well as the challenges for translating these methods into a visible biomedical instrument for biophysics and mechanobiology.